Evaluación y calificación de resúmenes de textos expositivos en el aula de ILE/IFE - Irina Argüelles Álvarez (Ibérica, 2004)
Students of English for Specific Purposes (ESP) need to summarize and to write summaries in the classroom when they work with expository texts related to their studies. If we adopt a pedagogical perspective where teaching and assessment are understood to be linked to the teaching-learning system, we will have to address the matter of how summaries written by students are assessed. If the required assessment is to be formative, it must provide answers to questions such as: What is good? What is poor? What can the student do to improve? In this case, not only the quality of the writing should be assessed but also the quality with which the writer transmits the message in general and, in particular, the main ideas from the original text. In the context of ESP, linguistic factors have also to be considered owing to their importance. Guides for the assessment of writing have been produced but it is difficult to find guides directed towards the assessment of summary writing. In this article, a number of well-known writing assessment proposals are reviewed and a new guide for the assessment of summaries of expository texts is presented